Identification of virulence genes and clade-specific markers through pan-genomic analysis of Leptospira - Mohd Abdullah; Mohammad Kadivella; Rolee Sharma; Mirza. S. Baig; Syed M. Faisal; Sarwar Azam (BMC Microbiology)
Abstract Leptospirosis is an emerging zoonotic and neglected disease across the world causing huge loss of life and economy. In this study, we did whole genome sequencing of one Leptospira isolate and a comparative genomic analysis with 69 other species of Leptospira available in RefSeq database provided insight into taxonomic and evolutionary relationship between species. AAI and whole genome based phylogenomic analysis established 3 clusters of Leptospira i.e. pathogenic, intermediate and saprophytic correlating with level of virulence of species. Leptospira has large closed core genome of 1038 genes and an open pan genome with 20,822 genes. The mobilome related genes were found mainly in pan-genome of pathogenic clade. A total of 498 genes have been identified as virulomes, with 329 virulent genes exhibiting presence/absence in various Leptospira species contributing to each species specific virulence profile. The hierarchical clustering of the congregated pathogenic genes yielded five groups, each with a distinct pattern of predominant genes that were either unique or common among clades, indicating lineage uniqueness. Most of the virulent gene pool identified were significantly enriched in COG functional categories of Nucleotide transport and metabolism, Intracellular trafficking, secretion and vesicular transport, cell motility and amino acid transport & metabolism. Pathogenic leptospires exhibit fewer clade-specific genes than non-pathogenic and intermediate leptospires, indicating gene loss and gain events in the evolution of pathogenic leptospires from non-pathogenic. The study’s clade-specific and virulent genes can be utilised as markers for defining clade and associated virulence levels in any new Leptospira isolates. Wet-lab validation of virulent genes will help in accurately targeting pathogenic pathways of Leptospira and controlling leptospirosis.